Rekomendasi Pengelolaan Kawasan Cagar Budaya Pelabuhan Boom dan Shipwreck di Pulau Bawean, Kabupaten Gresik - Dhony, Muslim Dimas Khoiru; Safitri, Laksmi Eko (JANUS, 2025)
The Boom Harbor Cultural Heritage Area and the shipwrecks off Bawean Island are significant cultural heritages that require sustainable management planning. This study aims to provide a concise overview of the management strategies for developing and utilizing the Boom Harbor Cultural Heritage Area and the shipwrecks. Data analyzed stem from the Decree of the Regent of Gresik No. 028/478/HK/437.12/2020, which establishes the Boom Harbor Area, and the cultural heritage recommendation file document number 432-3/009/TACB-Kab.Gresik/05/12/2016, which pertains to the shipwrecks. These documents highlight that these sites possess considerable historical, scientific, and cultural value. The planning strategy follows the guidelines outlined in the 2011 Historic Urban Landscape Recommendation (UNESCO), which identifies four key "instruments": community involvement, knowledge and planning tools, regulatory systems, and financing. By employing these instruments, we recommend collaborative programs among the Bawean Island community, local government, and the private sector, implementing them in stages and ensuring sustainability. === Kawasan Cagar Budaya Pelabuhan Boom dan shipwreck di Pulau Bawean merupakan Cagar Budaya yang memerlukan perencanaan pengelolaan yang berkelanjutan. Penelitian ini bertujuan untuk memberikan gambaran singkat strategi rencana pengelolaan dalam pengembangan dan pemanfaatan KCB Pelabuhan Boom dan shipwreck. Data yang diperoleh berdasarkan Surat Keputusan Bupati Gresik No. Bupati Gresik Nomor: 028/478/ HK/437.12/2020 tentang penetapan Kawasan Pelabuhan Boom dan berkas rekomendasi Cagar Budaya dokumen nomor: 432-3/009/TACB-Kab.Gresik/05/12/2016 mengenai shipwreck menunjukkan bahwa objek-objek tersebut memiliki nilai penting di bidang sejarah, ilmu pengetahuan, kebudayaan. Indikator strategi perencanaan merujuk pada Recommendation on The Historic Urban Landscape 2011 (UNESCO) dengan menggunakan empat instrumen seperti: civic engagement, knowledge and planning tools, regulatory sistem, dan financial. Penggunaan instrumen tersebut menghasilkan rekomendasi mengenai program kolaborasi antara masyarakat Pulau Bawean, pemerintah daerah dan pihak swasta yang dapat dilakukan secara bertahap serta berkelanjutan.